Identification of humid periods in the Atacama Desert through hillslope activity established by infrared stimulated luminescence (IRSL) dating - Medialdea, Alicia; May, Simon Matthias; Brill, Dominik; King, Georgina; Ritter, Benedikt; Wennrich, Volker; Bartz, Melanie; Zander, Anja; Kuiper, Klaudia; Hurtado, Santiago; Hoffmeister, Dirk; Schulte, Philipp; et al. (Global and planetary change, 2020)
Geological records indicate that the hyper-aridity in the Atacama Desert has prevailed since at least the mid-Miocene, with shorter periods of increased humidity punctuating long-term aridity. The 7-m-high accumulation of colluvial sediments at the Salar Grande (21°S/70°W) studied here provides a key palaeoclimate record to understand hillslope dynamics and its relation to humid periods. While 10Be surface exposure ages point to long-term surface stability of the flat upslope surface, a combination of humidity-driven soil creep, overland flow and soil creep related to seismic shaking, caused denudation of the hillslope and accumulation of several metres of colluvium over much shorter timescales during the last 130 ka. A robust chronology for the hillslope sediments has been established by using Infrared Stimulated luminescence (pIR-IR225 protocol) on K-feldspar extracts from nine samples collected within the accumulation. A series of tests has been carried out to confirm the suitability of the method. The estimated ages indicate accelerated sedimentation at 35-80 ka, and 100-130 ka, which are interpreted as periods with more humid climate conditions than present. These findings agree with climate variations in the hyper-arid Atacama indicated by the activity of coastal alluvial fans and river catchments.
Available online 29 November 2019
Gesehen am 02.04.2020